Pluralisme Nurcholis Madjid dan Relevansinya terhadap Problem Dakwah Kontemporer (Nurcholis Madjid’s Pluralism and Its Relevance to The Problem of Contemporary Da'wah) - Anja Kusuma Atmaja (Jurnal Dakwah Risalah, 2020)
This article aims to show Nurcholish Madjid's thoughts on national pluralism and to find its relevance to the issue of dakwah today. This type of research is library research and descriptive qualitative using the method of documentation and study of literature by gathering literature on Nurcholish Madjid thoughts related to pluralism. Content analysis is used to analyze the meaning contained in assumptions, ideas, or statements to get understanding and conclusions. In this article, the author found that the pluralism voiced by Nurcholish Madjid concerned three things, namely, humanity, justice, and tolerance. Given that, the preachers in our times are often found, when delivering their preachs, tend to be in a way that is far from moderation. For this reason, the thinking of Nurcholish Madjid on pluralism is still needed as solution in overcoming the problems of dakwah in the contemporary era.